2010
DOI: 10.1016/j.neuroscience.2010.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor expression and distribution dynamically change in the rat nucleus accumbens after withdrawal from cocaine self-administration

Abstract: Dopamine receptors (DARs) in the nucleus accumbens (NAc) are critical for cocaine's actions but the nature of adaptations in DAR function after repeated cocaine exposure remains controversial. This may be due in part to the fact that different methods used in previous studies measured different DAR pools. In the present study, we used a protein crosslinking assay to make the first measurements of DAR surface expression in the NAc of cocaine-experienced rats. Intracellular and total receptor levels were also qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
61
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 101 publications
(139 reference statements)
8
61
3
Order By: Relevance
“…All of these findings support a conclusion that D 3 R deletion leads to enhanced susceptibility to cocaine use and abuse. This conclusion appears to conflict with previous reports that cocaine overdose or chronic cocaine administration up-regulates D 3 R expression in the NAc in cocaine addicts or experimental animals (52)(53)(54)(55)(56). However, we point out that our finding that D 3 R deletion causes an increase in cocaine-taking and cocaine-seeking was observed during the acquisition and maintenance of cocaine self-administration and early extinction, whereas D 3 R up-regulation in the aforementioned studies was observed after prolonged abstinence (30-45 d of withdrawal from the last cocaine administration), not during self-administration or within 7 d of withdrawal (53,55,56).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…All of these findings support a conclusion that D 3 R deletion leads to enhanced susceptibility to cocaine use and abuse. This conclusion appears to conflict with previous reports that cocaine overdose or chronic cocaine administration up-regulates D 3 R expression in the NAc in cocaine addicts or experimental animals (52)(53)(54)(55)(56). However, we point out that our finding that D 3 R deletion causes an increase in cocaine-taking and cocaine-seeking was observed during the acquisition and maintenance of cocaine self-administration and early extinction, whereas D 3 R up-regulation in the aforementioned studies was observed after prolonged abstinence (30-45 d of withdrawal from the last cocaine administration), not during self-administration or within 7 d of withdrawal (53,55,56).…”
Section: Discussioncontrasting
confidence: 87%
“…This conclusion appears to conflict with previous reports that cocaine overdose or chronic cocaine administration up-regulates D 3 R expression in the NAc in cocaine addicts or experimental animals (52)(53)(54)(55)(56). However, we point out that our finding that D 3 R deletion causes an increase in cocaine-taking and cocaine-seeking was observed during the acquisition and maintenance of cocaine self-administration and early extinction, whereas D 3 R up-regulation in the aforementioned studies was observed after prolonged abstinence (30-45 d of withdrawal from the last cocaine administration), not during self-administration or within 7 d of withdrawal (53,55,56). Moreover, findings of D 3 R up-regulation were based on the use of lowselective D 3 /D 2 receptor ligands, such as [ 3 H]-7-OH-DPAT and [ 125 I]-7-OH-PIPAT, and no control experiments were conducted to rigorously identify the receptor-binding specificity of such ligands (52,53,55).…”
Section: Discussioncontrasting
confidence: 87%
“…Recent studies have demonstrated the importance of miRNAs in the pathophysiology of several neuropsychiatric disorders and mental retardation syndromes (Conrad et al 2010;Sulzer 2011), including schizophrenia (Burmistrova et al 2007;Beveridge et al 2010;Moreau et al 2011;Santarelli et al 2011), bipolar disorder, Fragile X mental retardation (Edbauer et al 2010;Krol et al 2010;Wulff et al 2011), Rett syndrome (Wu et al 2010), Alzheimer's disease, Parkinson's disease (Junn et al 2009), and Huntington's disease (Martí et al 2010). A number of the cocaine-responsive miRNAs identified in this study are important in controlling dendritic morphology; these miRNAs, and many others, may contribute to long-lasting forms of drugmediated synaptic plasticity through control of regulatory Lugli et al 2008 (adult mouse cortex and hippocampus; measured by microarray) with RNA-Seq data (adult mouse striatum) from these experiments (Lugli et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These molecules are differentially expressed in the bHR and bLR rat lines (19,29) and have been previously implicated in addiction-related behaviors (e.g., refs. [30][31][32]. We have shown that administration of FGF2 early in life increases the acquisition of cocaine self-administration in adulthood (33) and renders bLRs more bHR-like (34), supporting a role for FGF2 as a neuromolecular antecedent of drugtaking behavior (18,35).…”
mentioning
confidence: 81%